Penentuan Siswa Berprestasi Menggunakan Metode Analytical Hierarchy Process (AHP) dengan Pembobotan Entropy dalam Sistem Pendukung Keputusan - Sudarman, Dita Auliya; Irmayani, Deci; Masrizal, Masrizal; Ritonga, Ali Akbar (Building of Informatics, Technology and Science (BITS), 2025)
Determining outstanding students is one of the important aspects in the world of education to provide objective awards to students who have the best academic and non-academic achievements. This study aims to develop a decision support system (DSS) in determining outstanding students using the Analytical Hierarchy Process (AHP) method with Entropy weighting. The AHP method is used to determine the weight of the criteria based on pairwise comparisons, while the Entropy method is used to balance the weight based on data distribution. The results of the calculations in the system show that the alternative with the highest value is Habibi Altaqi (A18) with a value of 89,078, followed by Alif Alhafiz Syahputra (A25) and Sintya Azahra (A03) in second and third place. Conversely, the alternative with the lowest value is Eka (A10) with a value of 73,554, ranked 25th. The results of this study indicate that the AHP and Entropy methods are able to provide objective and systematic evaluations in the selection process of outstanding students. The system developed can be used as a tool for schools in making decisions more accurately and transparently. The contribution of this research is to provide an integrated approach between AHP and Entropy in a decision support system that can be adopted by other educational institutions to improve objectivity and accountability in the assessment process of high-achieving students.